2004
DOI: 10.1093/annonc/mdh150
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil induces arterial vasocontractions

Abstract: Application of 5-FU is commonly accompanied by arterial vessel contractions, which is likely to represent the first step in 5-FU-induced cardiotoxicity. 5-FU-associated vessel contractions were highly reproducible on re-exposure and were in the case of bolus application completely preventable by glyceroltrinitrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 19 publications
3
93
1
7
Order By: Relevance
“…Ultrasound and angiographic studies demonstrate both coronary artery and brachial artery vasospasm following 5-FU infusion [21][22][23]. Prior case reports reveal disease-free coronary arteries on angiography [24].…”
Section: Coronary Vasospasmmentioning
confidence: 96%
“…Ultrasound and angiographic studies demonstrate both coronary artery and brachial artery vasospasm following 5-FU infusion [21][22][23]. Prior case reports reveal disease-free coronary arteries on angiography [24].…”
Section: Coronary Vasospasmmentioning
confidence: 96%
“…Vasospasm is a reasonable mechanism, since it would explain reports of the effi cacy of vasodilating drugs given prophylactically to patients who experienced a previous episode of chest pain during 5-FU treatment 5,6 . Angina pectoris, acute myocardial infarction, congestive heart failure, cardiomyopathy, myopericarditis, ventricular and supraventricular tachycardia, prolonged QT interval, sudden death, cardiogenic shock and coronary dissection are counted among cardiotoxic eff ects of 5-FU 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Th e therapy was discontinued and the patient was transferred to our intensive care unit because the electrocardiogram (ECG) showed ischemic changes. Th e fi rst ECG showed ST elevation and peaked T waves in D I-III , aVL, aVF and V [2][3][4][5][6] derivations as well as reciprocal changes in aVR and V I ( Figure 1). Detailed history revealed that a coronary angiography revealing non-pathological fi ndings was performed two weeks ago as a result of a similar clinical picture in another center.…”
Section: Case Presentationmentioning
confidence: 99%
“…However, the pathogenic mechanism leading to cardiac injury is not fully understood and based off a limited number of studies, but thought to be due to coronary vasospasm from transient vasoconstriction. 20,21 Several studies have shown that both the coronary artery and brachial artery exhibit vasospasm after 5-FU administration. 20 Studies in animal models have shown a dose-related vasospasm that resolves after 5-FU is discontinued.…”
Section: Non-anthracyclinesmentioning
confidence: 99%
“…20 Studies in animal models have shown a dose-related vasospasm that resolves after 5-FU is discontinued. 21 Other potential causes are endothelial damage and transient stress-induced cardiomyopathies, as well as coronary thrombosis and arteritis, leading to manifestations such as asymptomatic EKG changes to acute pulmonary edema, arrhythmias, and myocardial infarctions with ST segment and cardiac biomarker elevations. 22 The risk of cardiotoxicity of 5-FU depends on the route and schedule of administration but is not necessarily dependent on underlying cardiovascular disease.…”
Section: Non-anthracyclinesmentioning
confidence: 99%